Desarrollo e implementación de los módulos de: plan de cuentas, recursos humanos, contabilidad, reportes y seguridad, integrados al sistema contable "Gesv" para la empresa "La mejor compra" utilizando Java y base de datos Postgresql - Montesinos Fernández, Sofía Valeria (2013)
"LA MEJOR COMPRA" The company has a rudimentary accounting system in an Excel spreadsheet that does not guarantee the security of information. In this regard, the objectives that were raised in this research was to automate operational business processes, solve specific problems, fulfilling functional and non-functional requirements with the customer and provide a safe, easy and adaptable to changes in product advancement technology.